Os centros de especialidades odontológicas e o cuidado em saúde bucal da pessoa com necessidades especiais - Targino, Mariana Pereira dos Santos (2024)
People with Special Needs (PNE) are a group of people who need care and attention to their health, especially in rehabilitation processes. The National Program for Improving Access and Quality in Dental Specialty Centers (PMAQ-CEO) is a tool for evaluating the evolution of care for PNE. The aim of this study is to analyze the characteristics of the evolution of the provision of care for SNEs in Dental Specialty Centers (DSC). This is a cross-sectional, descriptive, quantitative study using secondary data, comparing the two PMAQ-CEO cycles. Inclusion and exclusion criteria were applied and the sample consisted of 850 DSCs. Variables were selected according to the following blocks: professional profile, access, accessibility and equipment. The analysis was carried out using JAMOVI 2.4.8 software, using distributions and frequencies. Associations were verified using McNemar's test and CI performed in SPSS 29.0. The results point to accessibility, quantity and qualifications of professionals as the characteristics of dental service provision for PSNs in the 1st and 2nd cycles of the PMAQ-CEO. The evolution of secondary dental care provided to PSNs in Brazil between the PMAQ-CEO cycles (2013-2018), according to the methodology of this study, showed a positive evolution, highlighting the number of PSN professionals, their academic qualifications, accessibility, access and network flow. The negative points identified were the PNE CD's workload without progress, the repressed demand and the lack of sedation equipment. Improving care for the PNE could benefit from continued monitoring, identifying critical points to be tackled in the service.